Relationship between urinary sodium‐to‐potassium ratio and ambulatory blood pressure in patients with diabetes mellitus. (25th October 2017) - Libianto, Renata; Moran, John; O'Callaghan, Christopher; Baqar, Sara; Chen, Angela X; Baker, Scott T; Clarke, Michelle; MacIsaac, Richard J; Jerums, George; Ekinci, Elif I
Summary: Previous studies investigating the relationship between sodium intake and blood pressure have mostly relied on dietary recall and clinic blood pressure measurement. In this cross‐sectional study, we aimed to investigate the relationship between 24 hour urinary sodium and potassium excretion, and their ratio, with 24 hour ambulatory blood pressure parameters including nocturnal blood pressure dipping in patients with type 1 and 2 diabetes. We report that in 116 patients with diabetes, systolic blood pressure was significantly predicted by the time of day, age, the interaction between dipping status with time, and 24 hour urinary sodium‐to‐potassium ratio ( R 2  = 0.83) with a relative contribution of 53%, 21%, 20% and 6%, respectively. However, there was no interaction between urinary sodium‐to‐potassium ratio and dipping status.